The state of food and agriculture 1997. (Rome Food and Agriculture Organization of the United Nations, 1997)
The special chapter, The Agroprocessing industry and economic development: "examines the role of the agroprocessing industry in economic development, the changes in conditions for agro-industrial development worldwide and the implications of such chan ges for developing countries"--P. [4] of cover.
The special chapter, The Agroprocessing industry and economic development: "examines the role of the agroprocessing industry in economic development, the changes in conditions for agro-industrial development worldwide and the implications of such chan ges for developing countries"--P. [4] of cover.
The statistical material in this publication has been prepared from the information available to FAO up to July 1997"--T. p. verso.
Title on diskette: Time series for SOFA '97. "The time series data is presented in English, French and Spanish and includes agricultural, fisheries and forestry data for a large number of countries and country groups"--P. [4] of cover.
System requirements for accompanying disk: IBM or compatible PC; 300 KB RAM; DOS 3.0 or higher; VGA, EGA, MCGA, CGA or Hercules monochrome.
Keywords: Agriculture; Agro-industrial complexes; Food production; Food security